Airline self-service technology adoption: Moderating impact of gender and experience - Harsandaldeep Kaur; Parmeet Kaur (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of the paper is to examine the role of technology paradoxes, including technology anxiety, insecurity and forced usage, to understand consumer adoption behavior towards self-service technology. The present study also investigates the moderating effect of gender and experience on the relationship between paradoxes and adoption attitude towards self-service technology. Design/methodology/approach: In this study, a quantitative research approach was employed. We tested the research hypotheses using survey data collected from 249 users of self-service technology in the airline sector. Further, we tested the structural path relationship using SmartPLS-4. Findings: The findings have revealed the significant impacts of technology anxiety and insecurity on adoption attitude. The findings also reveal the partial moderating roles of gender and experience in the link between paradoxes and adoption attitude. Research limitations/implications: This study does not consider other factors influencing consumer adoption of self-service technology, such as ease of use, trust, and speed. The present study relies on cross sectional data to study consumer attitudes. Longitudinal research is required to examine consumer adoption attitudes towards technology in long run. Originality/value: The present study contributes to literature by investigating the role of paradoxes to understand consumer adoption attitudes and also determine the strategies that must be focused upon by service providers to enhance the experience of customers using self-service technology.
Keywords: 650; Self-service technology; Technology anxiety; Insecurity; Forced usage; Adoption attitude